Transformational educational leaders inspire school educators’ commitment - Kareem, Jacqueline; Patrick, Harold Andrew; Prabakaran, Nepoleon; B, Valarmathi; Tantia, Veerta; M. P. M., Pramod Kumar; Mukherjee, Ujjal (Frontiers in Education, 2023)
Transformational school leaders play an important role in promoting educational innovation and restructuring by creating a vision for the future, building a culture of collaboration, and empowering others to become leaders themselves. Through their leadership style, they inspire and motivate others to work towards a common goal, leading to positive change and growth within the educational system. The purpose of this study is to measure the influence of transformational leadership on different types of commitment that school teachers have. The study used standardised instruments to measure the leadership style of principals and personal commitment of teachers. This study was conducted in the Indian city of Bengaluru. The data was collected from 1,173 school teachers through the questionnaire that measured the leadership styles and personal commitment of teachers. The data was treated through the SPSS V23 statistical software for the analysis. The study found that transformational leadership had a significant effect in the path of different types commitment that teachers possessed in school education. To facilitate organisational learning through more integrative methods, leaders of school management are advised to take into account three domains of the commitments of their teachers - commitment towards the institution, student development and self-development.